Critical race theory in LIS : challenging white supremacy in libraries - Colón-Aguirre, Mónica; Cooke, Nicole A.; Johnson, Aisha M.; Collins, Anastasia M. (Advances in librarianship ;, 2025)
This volume shares some of the ways that librarians and library scholars are incorporating Critical Race Theory (CRT) into the field of library and information studies. CRT provides a theoretical and analytical lens through which librarians can challenge the ways race and racism harm shape library access, collections, discourses, and services, with the goal of instigating changes that lead to social justice. Chapter authors represent different points of views related to CRT from their unique perspective as members of minoritized groups and contributions move beyond generalized language and tackle topics directly related to race in America and how these affect the work in libraries. The way in which libraries and other information professions perpetuate racism are explored, alongside racist practices, as well as ideas on how information professionals can move beyond these systems and create institutions that support their patrons and create environments in which all are welcomed. Critical Race Theory in LIS fulfills a need for LIS literature to focus on race issues in the profession. The work is related to the larger umbrella of DEI work and will advance Social Justice issues in the profession but from a race perspective.